2020
DOI: 10.3892/ol.2020.12125
|View full text |Cite
|
Sign up to set email alerts
|

LINC00294 induced by GRP78 promotes cervical cancer development by promoting cell cycle transition

Abstract: Cervical cancer is one of the most common gynecological malignancies, and it has become a crucial public health problem. In the present study, the expression profiles of cervical cancer and normal cervical tissues were downloaded from the Gene Expression Omnibus and The Cancer Genome Atlas databases. Subsequently, the dysregulated long non-coding RNAs (lncRNAs) in cervical cancer were identified using R software Differentially expressed lncRNAs in cervical cancer that were associated with glucose-regulated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Notably, the aberrant lncRNA expression is implicated in glioma initiation and progression, and consequently, lncRNAs can function as competent biomarkers for the diagnosis, prognosis, and target therapy of glioma [ 13 ]. Qiu et al have revealed that LINC00294 facilitates cervical cancer progression by regulation of the cell cycle via the Hedgehog pathway [ 14 ]. Notably, the NONCODE database indicated that LINC00294 is upregulated in the normal brain tissues, and GEPIA suggests that LINC00294 is notably downregulated in glioblastoma (GBM) tissues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the aberrant lncRNA expression is implicated in glioma initiation and progression, and consequently, lncRNAs can function as competent biomarkers for the diagnosis, prognosis, and target therapy of glioma [ 13 ]. Qiu et al have revealed that LINC00294 facilitates cervical cancer progression by regulation of the cell cycle via the Hedgehog pathway [ 14 ]. Notably, the NONCODE database indicated that LINC00294 is upregulated in the normal brain tissues, and GEPIA suggests that LINC00294 is notably downregulated in glioblastoma (GBM) tissues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, NEFM, a tumor suppressor, was reported to be significantly reduced in cancerous conditions and boost in glioma cells through LINC00294 up-regulation [ 50 ]. LINC00294 induced by GRP78 may still promote the progression of cervical cancer [ 51 ]. In addition, Bak-IIIa may improve LPS-induced inflammatory damage in HUVECs through upregulating LINC00294 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, GRP78 is one of the markers of cancer stem cells [ 15 ]. The high expression of GRP78 could promote the stem cell-like properties of cervix cancer [ 25 ]. Interestingly, we also noticed here that EIF3D could promote the stem cell-like properties of cervix cancer via GRP78.…”
Section: Discussionmentioning
confidence: 99%